2005
DOI: 10.1007/s00394-005-0557-8
|View full text |Cite
|
Sign up to set email alerts
|

Stability and biotransformation of various dietary anthocyanins in vitro

Abstract: The gut microflora seem to play an important role in the biotransformation of anthocyanins. A rapid degradation could be one major reason for the poor bioavailability of anthocyanins in pharmacokinetic studies described so far in the literature. The formation of phenolic acids as the major stable degradation products gives an important hint to the fate of anthocyanins in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
252
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(277 citation statements)
references
References 20 publications
16
252
0
9
Order By: Relevance
“…Microbiota can degrade anthocyanins to phenolic acids and aldehydes by splitting the C-ring and modifying the remaining A and B-rings (62) . Some of the main metabolites of microbiota degradation are gallic acid, vanillic acid, homovanilic acid, protocatechuic acid (PCA), syringic acid and 4-hydroxybenzoic acid (55,(65)(66)(67)(68) . Despite knowledge of the high rate of anthocyanin degradation by gut microbiota there is still no consensus about the proportion absorbed into the systemic circulation (45,53,55) .…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
“…Microbiota can degrade anthocyanins to phenolic acids and aldehydes by splitting the C-ring and modifying the remaining A and B-rings (62) . Some of the main metabolites of microbiota degradation are gallic acid, vanillic acid, homovanilic acid, protocatechuic acid (PCA), syringic acid and 4-hydroxybenzoic acid (55,(65)(66)(67)(68) . Despite knowledge of the high rate of anthocyanin degradation by gut microbiota there is still no consensus about the proportion absorbed into the systemic circulation (45,53,55) .…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
“…Several studies have demonstrated possible beneficial effects of anthocyanins on chronic degenerative diseases, including CVD and cancer (Tsuda et al, 1996;Prior and Cao, 2000;Kay and Holub, 2002;Nakamura et al, 2002;Hou, 2003;Kang et al, 2003;Xu et al, 2004;Rechner and Kroner, 2005;Dalgard et al, 2009). Anthocyanins have low bioavailability (Kay, 2006;Hollands et al, 2008) and are metabolised in humans into methylated derivatives, glucuronides and sulfoconjugates (Wu et al, 2002;Felgines et al, 2003Felgines et al, , 2005Kay et al, 2004Kay et al, , 2005, but phenolic acids are the major stable metabolites of anthocyanins in vivo (Keppler and Humpf, 2005;Fleschhut et al, 2006). Endothelial cell dysfunction is a critical initiating event in the progression of atherosclerosis (Ross, 1999), but the effects of anthocyanins on endothelial function at normal intake levels have not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions could take place due to intestinal microflora (Aura et al, 2005b;Ávila et al, 2009;Fleschhut et al, 2006), under intestinal conditions at pH 7 (Fleschhut et al, 2006), or spontaneously in the presence of intestinal epithelial cells (Hassimotto et al, 2008;Kay et al, 2009). Degradation of anthocyanidin aglycon, achieved spontaneously or by microflora (Ávila et al, 2009;Fleschhut et al, 2006;Forester and Waterhouse, 2008), represents the breakdown of its heterocycle and cleavage of the C-ring to form phenolic acid and aldehyde (Keppler and Humpf, 2005). Spontaneous degradation is a consequence of the neutral pH because anthocyanidin aglycones are observed in chalcone form which is rather unstable and can be easily degraded (Fleschhut et al, 2006;Keppler and Humpf, 2005).…”
Section: Fate Of Anthocyanins In the Gastro-intestinal Tractmentioning
confidence: 99%
“…Later, their degradation was demonstrated by two steps. The first step is deglycosylation of anthocyanins to anthocyanidin aglycon while the second step is degradation of the formed aglycon to phenolic acid and aldehyde (Ávila et al, 2009;Fleschhut et al, 2006). Deglycosylation is the cleavage of the glycosyl moiety from anthocyanins structure to form anthocyanidin aglycons.…”
Section: Fate Of Anthocyanins In the Gastro-intestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation